The Autism Diagnostic Observation Schedule-Generic: A Standard Measure of Social and Communication Deficits Associated with the Spectrum of Autism - Lord, Catherine; Risi, Susan; Lambrecht, Linda; Cook, Edwin H., Jr; Leventhal, Bennett L; DiLavore, Pamela C; Pickles, Andrew; Rutter, Michael (Journal of autism and developmental disorders, 2000)
Psychometric data are presented for 223 children and adults with autism, pervasive developmental disorder not otherwise specified (PDDNOS), or nonspectrum diagnoses who took the Autism Diagnostic Observation Schedule-Generic. Within each module, diagnostic groups were equivalent on expressive language levels. Results indicate substantial interrater and test-retest reliability and excellent internal consistency. (Contains references.) (Author/CR)